2012
DOI: 10.1007/s12032-012-0256-2
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of SBRT of metastases in patients with primary sarcoma

Abstract: We retrospectively reviewed the results of stereotactic body radiotherapy (SBRT) in 46 patients with a total of 136 metastases from primary sarcoma. The purpose of this study was to evaluate the overall response rate and side effects of SBRT in metastatic sarcoma. The patients were treated at Karolinska University Hospital between 1994 and 2005, using 3D conformal multifield technique and a stereotactic body-frame. Prescribed doses ranged from 4 to 20 Gy per fraction in 1–5 fractions, with total doses of 10–48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…Those authors concluded that SBRT is an effective and safe treatment for patients with metastatic sarcoma. 6 Dhakal and colleagues described 15 patients treated by SBRT for metastatic soft-tissue sarcoma to the lung. Seventy-four lesions were treated with 50 Gy in 5 fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors concluded that SBRT is an effective and safe treatment for patients with metastatic sarcoma. 6 Dhakal and colleagues described 15 patients treated by SBRT for metastatic soft-tissue sarcoma to the lung. Seventy-four lesions were treated with 50 Gy in 5 fractions.…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of patients with sarcoma will experience metastases during the course of the disease. The median overall survival for metastatic sarcomas went from 12 months in the 1990s [5] to 18e24 months in recent studies [6,7]. Local treatments have increasingly been used in recent years for cases of sarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Literature data suggests various, but often low alpha/beta ratio of sarcomas, mostly between 0.4 and 5 Gy [16]. Thus, we assumed alpha/beta ratio of sarcomas as 3 to calculate EQD2 [17].…”
Section: Radiotherapymentioning
confidence: 99%